PERAN PEMERINTAH DALAM PENGELOLAAN PROGRAM CSR DI KABUPATEN TRENGGALEK (Studi Implementasi Peraturan Daerah Provinsi Jawa Timur Nomor 4 Tahun 2011 Tentang Tanggungjawab Sosial Perusahaan) - Reban, Reban; Fachruddin, Imam (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
The realization of the Corporate Social Responsibility Program (CSR) of industry in Trenggalek regency has been arranged in District Regulation Number  3, 2016 It is about corporate social responsibility. A reason for the realization of this program is fund limitation or government funding in development, so it needs attention, motivation and cooperation from corporate to participate and be responsible towards the development. In the environment. This research aims to know the government's role in Trenggalek regency in case of management for the realization of the CSR program and the advantage of this program forward Trenggalek regency development. Data resources or informants in this research are management facilitate the team of the CSR program. This research used a Qualitative data analysis method. The results of this research show that the government has a very strategic role in the management of the realization of the CSR program, that is the government as the data/ information provider, planner and the manager of monitoring and evaluation forward the realization of the CSR Program. The advantage of the achievement of the CSR Program has been enjoyed by Society, like public facilities for daily life or education.